PENGKAJIAN TENTANG STRATEGI KEHIDUPAN KELUARGA BURUH MISKIN - Soetji Andari (Sosio Informa, 2005)
Studi Kasus Tentang Buruh Tani Di Desa Cibodas Kecamatan Lembang Kabupaten Bandung -(Case Study of the Life of Peasant Families in Cibodas Village, Bandung).This research represents a case study of howpeasant families eam income to support their lives. These problems if could not be overcome overcoming will generate the problems effect the functioning social of role in this society. Social capital represents an alternative in realizingconsanquinity link. Related pattern of client patron and also vertical relation among farmlandwith the existing local institute, not even give the resilience to farmworker strategy in living on, but also will be powered of impecunious family in overcoming its life problems.